A SYSTEMATIC REVIEW OF BEHAVIOURAL CHANGES IN L1 LEARNERS DUE TO L2 NONVERBAL CUES - Vindhyavali, S (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This systematic review explores the influence of second language (L2) nonverbal cues on first language (L1) behaviours among learners. While existing research has primarily focused on verbal proficiency, the integration of nonverbal communication—encompassing gestures, facial expressions, body posture, and vocal tone—into L2 learning remains under examined. This study investigates the phenomenon of superimposition, where L2 learners adopt nonverbal cues that subsequently shape their L1 interactions. Through an interdisciplinary lens incorporating psycholinguistics, cross-cultural communication, and second language acquisition theories, we identify significant behavioural changes in L1 communication patterns, emotional expressiveness, and social interaction styles. Key areas of impact include alterations in facial expressions, gestural behaviours, eye contact, and paralanguage. Utilizing psychometric tools such as self-report surveys, observational studies, and vocal analysis, this review highlights the complexities of nonverbal communication across languages and cultures. Ultimately, our findings underscore the necessity of understanding nonverbal cue integration to enhance cross-cultural communication and support multilingual individuals in navigating diverse interaction contexts.